Unlocking the potential of dimethyl fumarate: enhancing oncolytic HSV-1 efficacy for wider cancer applications - Alwithenani, Akram; Taha, Zaid; Thomson, Max; Chen, Andrew; Wong, Boaz; Arulanandam, Rozanne; Diallo, Jean-Simon (Frontiers in Immunology, 2023)
Immunotherapy and specifically oncolytic virotherapy has emerged as a promising option for cancer patients, with oncolytic herpes simplex virus-1 (oHSV-1) expressing granulocyte macrophage colony stimulating factor being the first OV to be approved by the FDA for treatment of melanoma. However, not all cancers are sensitive and responsive to oncolytic viruses (OVs). Our group has demonstrated that fumaric and maleic acid esters (FMAEs) are very effective in sensitizing cancer cells to OV infection. Of note, these FMAEs include dimethyl fumarate (DMF, also known as Tecfidera®), an approved treatment for multiple sclerosis and psoriasis. This study aimed to assess the efficacy of DMF in combination with oncolytic HSV-1 in preclinical cancer models. We demonstrate herewith that pre-treatment with DMF or other FMAEs leads to a significant increase in viral growth of oHSV-1 in several cancer cell lines, including melanoma, while decreasing cell viability. Additionally, DMF was able to enhance ex vivo oHSV-1 infection of mouse-derived tumor cores as well as human patient tumour samples but not normal tissue. We further reveal that the increased viral spread and oncolysis of the combination therapy occurs via inhibition of type I IFN production and response. Finally, we demonstrate that DMF in combination with oHSV-1 can improve therapeutic outcomes in aggressive syngeneic murine cancer models. In sum, this study demonstrates the synergistic potential of two approved therapies for clinical evaluation in cancer patients.